Steiner triple systems intersecting in pairwise disjoint blocks - Chee, Yeow Meng (2010)
Two Steiner triple systems (X,A) and (X,B) are said to intersect in m pairwise disjoint blocks if |A ∩ B| = m and all blocks in A ∩ B are pairwise disjoint. For each v, we completely determine the possible values of m such that there exist two Steiner triple systems of order v intersecting in m pairwise disjoint blocks.